2007
DOI: 10.1021/cm070421g
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Electrochemistry of Copper Fluoride Nanocomposites Utilizing Mixed Conducting Matrices

Abstract: Near-theoretical utilization of high-energy-density CuF 2 positive electrode materials for lithium batteries was enabled through the use of nanocomposites consisting of 2-30 nm domains of CuF 2 within a mixed ionic + electronic conducting matrix of a metal oxide. Small but significant crystallographic changes to the core crystal of the CuF 2 were found to occur in all oxide-based matrices. These modifications to the core crystal and the surrounding matrix were investigated through a host of characterization me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
162
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(171 citation statements)
references
References 23 publications
9
162
0
Order By: Relevance
“…Such nanocomposites enable close-to-theoretical capacities, most of which is delivered at high voltages (close to 3 V). [ 271 ] Although these fi ndings are of certain interest in view of application in primary cells, reversibility of the reactions is not discussed. The reduction reaction has been recently studied by solid state NMR and XRD [ 272 ] and found to simply consist of direct formation of Cu and LiF without intermediate phases.…”
Section: Cobalt Nickel Coppermentioning
confidence: 99%
“…Such nanocomposites enable close-to-theoretical capacities, most of which is delivered at high voltages (close to 3 V). [ 271 ] Although these fi ndings are of certain interest in view of application in primary cells, reversibility of the reactions is not discussed. The reduction reaction has been recently studied by solid state NMR and XRD [ 272 ] and found to simply consist of direct formation of Cu and LiF without intermediate phases.…”
Section: Cobalt Nickel Coppermentioning
confidence: 99%
“…The MCM approach focuses mainly on effective transport of both ions and electrons to the metal fluoride nanodomain. It has been found that introduction of V 2 O 5 to the electro-active material can markedly enhance the electrochemical performance of the composite cathode [17,18]. Additionally, the density of V 2 O 5 is much higher than that of carbon, and the addition of V 2 O 5 is in favor of enhancing the specific energy density of cathode material.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the use of conversion materials with particular attention to metal oxides has been provided [96]. Copper fluoride CuF 2 nanocomposites within a mixed conduction matrix have shown almost stoichiometric conversion [97].…”
Section: Conversion Materialsmentioning
confidence: 99%